Carbide alloy and cutting tool using same
A cemented carbide composition with specific vanadium and chromium distribution improves tool life by enhancing hardness and wear resistance, addressing the challenge of short tool life in semiconductor substrate processing.
Patent Information
- Application Number
- JP2023565404
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2023-06-21
- Publication Date
- 2025-01-17
- Estimated Expiration
- 2043-06-21
AI Technical Summary
Existing cutting tools used for processing semiconductor package substrates face challenges in achieving a long tool life due to the demands of high precision and small-diameter drilling, which leads to increased costs and reduced efficiency.
A cemented carbide composition comprising 80% or more tungsten carbide particles and a binder phase with specific atomic percentages of vanadium and chromium, along with a cobalt binder, exhibits a unique atomic distribution pattern that enhances grain growth suppression and wear resistance, leading to improved tool life.
The cemented carbide composition results in cutting tools with extended tool life, particularly for semiconductor package substrates, by providing enhanced hardness, wear resistance, and breakage resistance.
Smart Images

Figure 0007616426000005 
Figure 0007616426000006 
Figure 0007616426000007
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a cemented carbide and a cutting tool using the same. [Background technology]
[0002] 2. Description of the Related Art Cemented carbide having tungsten carbide (WC) particles and a binder phase mainly composed of cobalt or the like has been used as a material for cutting tools (Patent Documents 1 and 2). [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2016-098393 A [Patent Document 2] JP 2021-110010 A Summary of the Invention
[0004] The cemented carbide of the present disclosure is A cemented carbide comprising a plurality of tungsten carbide particles and a binder phase, The cemented carbide contains 80% by volume or more of the tungsten carbide particles and the binder phase in total, The cemented carbide contains the binder phase in an amount of 0.1% by volume or more and 20% by volume or less, The cemented carbide contains vanadium in an amount of 0.03 atomic % or more and 0.90 atomic % or less, The cemented carbide contains 0.01 atomic % or more and 1.20 atomic % or less of chromium, The binder phase contains 50% by mass or more of cobalt, In a first region of a first graph, the results of a line analysis performed using an energy dispersive X-ray spectrometer attached to a transmission electron microscope along a first direction from a position X1 in the tungsten carbide particle to a position X2 in the binder phase adjacent to the tungsten carbide particle are plotted in a coordinate system in which the X axis represents the distance from position X1 and the Y axis represents the intensity, Maximum Strength of Tungsten IW Distance P at W and the maximum intensity I W 70% of the strength I W70 The maximum distance P W70 and the maximum strength of vanadium I V Distance P at V and the maximum strength of chromium I Cr Distance P at Cr and the maximum intensity of cobalt I Co 70% of the strength I Co70 The smallest distance P that indicates Co70 and the maximum intensity I Co Distance P at Co By P W <P W70 <P V <P Cr <P Co70 <P Co The relationship between The first region is a region in which the X-axis of the first graph corresponds to the P V From the distance P1, which is 3 nm from the origin of the coordinate system, V to a distance P2 that is 3 nm away from the origin. [Brief description of the drawings]
[0005] [Figure 1] FIG. 1 is a schematic cross-sectional view of a cemented carbide according to a first embodiment. [Diagram 2] FIG. 2 shows an example of a first graph of the cemented carbide according to the first embodiment. [Diagram 3] Figure 3 is a high-angle annular dark field (HAADF) image of a cross section of a cemented carbide alloy. [Figure 4] FIG. 4 is a diagram for explaining a method for confirming that vanadium atoms and chromium atoms are present in the C site of tungsten carbide. [Diagram 5] FIG. 5 is a schematic diagram of a cutting tool according to the second embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0006] [Problem that this disclosure aims to solve] With the expansion of 5G (5th generation mobile communication system), the demand for semiconductor package substrates is increasing. Holes are drilled in semiconductor package substrates using small diameter drills. From the viewpoint of cost reduction, cutting tools with long life are required even when used for processing semiconductor package substrates.
[0007] Therefore, an object of the present disclosure is to provide a cemented carbide alloy that, when used as a cutting tool material, can provide a cutting tool having a long tool life, particularly in processing semiconductor package substrates, and a cutting tool equipped with the same.
[0008] [Effects of this disclosure] According to the present disclosure, it is possible to provide a cemented carbide alloy that, when used as a cutting tool material, can provide a cutting tool having a long tool life, particularly in processing semiconductor package substrates, and a cutting tool including the same.
[0009] [Description of the embodiments of the present disclosure] First, the embodiments of the present disclosure will be listed and described. (1) The cemented carbide disclosed herein is A cemented carbide comprising a plurality of tungsten carbide particles and a binder phase, The cemented carbide contains 80% by volume or more of the tungsten carbide particles and the binder phase in total, The cemented carbide contains the binder phase in an amount of 0.1% by volume or more and 20% by volume or less, The cemented carbide contains vanadium in an amount of 0.03 atomic % or more and 0.90 atomic % or less, The cemented carbide contains 0.01 atomic % or more and 1.20 atomic % or less of chromium, The binder phase contains 50% by mass or more of cobalt, In a first region of a first graph, the results of a line analysis performed using an energy dispersive X-ray spectrometer attached to a transmission electron microscope along a first direction from a position X1 in the tungsten carbide particle to a position X2 in the binder phase adjacent to the tungsten carbide particle are plotted in a coordinate system in which the X axis represents the distance from position X1 and the Y axis represents the intensity, Maximum Strength of Tungsten I W Distance P at W and the maximum intensity I W 70% of the strength I W70 The maximum distance P W70 and the maximum strength of vanadium I V Distance P at V and the maximum strength of chromium I Cr Distance P at Cr and the maximum intensity of cobalt I Co 70% of the strength I Co70 The smallest distance P that indicates Co70 and the maximum intensity I Co Distance P at Co By P W <P W70 <P V <P Cr <P Co70 <P Co The relationship between The first region is a region in which the X-axis of the first graph corresponds to the P V From the distance P1, which is 3 nm from the origin of the coordinate system, V to a distance P2 which is 3 nm away from the origin.
[0010] According to the present disclosure, it is possible to provide a cemented carbide alloy that, when used as a cutting tool material, can provide a cutting tool having a long tool life, particularly in processing semiconductor package substrates, and a cutting tool including the same.
[0011] (2) In the above (1), the P V and the vanadium atom located at Cr The chromium atom located at may be present at the W site of tungsten carbide.
[0012] (3) In the above (1) or (2), the cemented carbide may contain 18 volume % or less of the binder phase, which further improves the tool life.
[0013] (4) A cutting tool according to the present disclosure is a cutting tool having a cutting edge made of the cemented carbide according to any one of (1) to (3) above.
[0014] The cutting tools of the present disclosure can have long tool life, especially when used in machining semiconductor package substrates.
[0015] [Details of the embodiment of the present disclosure] Specific examples of the cemented carbide and cutting tool of the present disclosure will be described below with reference to the drawings. In the drawings of the present disclosure, the same reference numerals represent the same or corresponding parts. Furthermore, dimensional relationships such as length, width, thickness, and depth have been appropriately changed for clarity and simplification of the drawings, and do not necessarily represent actual dimensional relationships.
[0016] In this disclosure, an expression in the form "A to B" means the upper and lower limits of a range (i.e., A or more and B or less). When no unit is specified for A and a unit is specified only for B, the unit of A and the unit of B are the same.
[0017] In the present disclosure, when a compound or the like is represented by a chemical formula, unless the atomic ratio is particularly limited, it is intended to include any conventionally known atomic ratio, and should not necessarily be limited to only those within the stoichiometric range.
[0018] In the present disclosure, when one or more numerical values are described as the lower limit and the upper limit of a numerical range, a combination of any one numerical value described as the lower limit and any one numerical value described as the upper limit is also disclosed. For example, when a1 or more, b1 or more, and c1 or more are described as the lower limit, and a2 or less, b2 or less, and c2 or less are described as the upper limit, a1 or more and a2 or less, a1 or more and b2 or less, a1 or more and c2 or less, b1 or more and a2 or less, b1 or more and b2 or less, b1 or more and c2 or less, c1 or more and a2 or less, c1 or more and b2 or less, and c1 or more and c2 or less are disclosed.
[0019] [Embodiment 1: Carbide] The cemented carbide according to one embodiment of the present disclosure (hereinafter also referred to as "embodiment 1") is A cemented carbide comprising a plurality of tungsten carbide particles and a binder phase, The cemented carbide contains 80% by volume or more of the tungsten carbide particles and the binder phase in total, The cemented carbide contains the binder phase in an amount of 0.1% by volume or more and 20% by volume or less, The cemented carbide contains vanadium in an amount of 0.03 atomic % or more and 0.90 atomic % or less, The cemented carbide contains 0.01 atomic % or more and 1.20 atomic % or less of chromium, The binder phase contains 50% by mass or more of cobalt, In a first region of a first graph, the results of a line analysis performed using an energy dispersive X-ray spectrometer attached to a transmission electron microscope along a first direction from a position X1 in the tungsten carbide particle to a position X2 in the binder phase adjacent to the tungsten carbide particle are plotted in a coordinate system in which the X axis represents the distance from position X1 and the Y axis represents the intensity, Maximum Strength of Tungsten I W Distance P at W and the maximum intensity I W 70% of the strength I W70 The maximum distance P W70 and the maximum strength of vanadium I V Distance P at V and the maximum strength of chromium I CrDistance P at Cr and the maximum intensity of cobalt I Co 70% of the strength I Co70 The smallest distance P that indicates Co70 and the maximum intensity I Co Distance P at Co By P W <P W70 <P V <P Cr <P Co70 <P Co The relationship between The first region is a region in which the X-axis of the first graph corresponds to the P V From the distance P1, which is 3 nm from the origin of the coordinate system, V to a distance P2 that is 3 nm away from the origin.
[0020] When the cemented carbide of the embodiment 1 is used as a material for a cutting tool, it is possible to provide a cutting tool having a long tool life, particularly in processing semiconductor package substrates. The reason for this is not clear, but is presumed to be as follows.
[0021] The cemented carbide of the first embodiment includes a plurality of tungsten carbide particles (hereinafter also referred to as "WC particles") and a binder phase, and the total content of the WC particles and the binder phase in the cemented carbide is 80 volume % or more. As a result, the cemented carbide has high hardness and strength, and a cutting tool using the cemented carbide can have excellent wear resistance and breakage resistance.
[0022] The cemented carbide of the first embodiment contains a binder phase of 0.1% by volume or more and 20% by volume or less, and the binder phase contains 50% by mass or more of cobalt. As a result, the cemented carbide has high hardness and strength, and a cutting tool using the cemented carbide can have excellent wear resistance and breakage resistance.
[0023] The cemented carbide of the first embodiment contains vanadium in an amount of 0.03 atomic % or more and 0.90 atomic % or less, and chromium in an amount of 0.01 atomic % or more and 1.20 atomic % or less. Vanadium and chromium have an effect of inhibiting the grain growth of tungsten carbide particles. Furthermore, in the cemented carbide of the first embodiment, P W <P W70 <P V <P Cr <P Co70 <P Co This shows the relationship between the grain growth suppression effect of the tungsten carbide particles and the hard alloy of the first embodiment. Therefore, the formation of abnormal structure due to the generation of coarse particles is suppressed in the hard alloy of the first embodiment, and the cutting tool using the hard alloy can have excellent breakage resistance.
[0024] <Composition of cemented carbide> As shown in FIG. 1, the cemented carbide 3 of the first embodiment includes a plurality of tungsten carbide particles 1 (hereinafter also referred to as "WC particles") and a binder phase 2, and the total content of the WC particles and the binder phase of the cemented carbide 3 is 80% by volume or more. The lower limit of the total content of the WC particles and the binder phase of the cemented carbide may be 82% by volume or more, 84% by volume or more, 85% by volume or more, or 86% by volume or more. The upper limit of the total content of the WC particles and the binder phase of the cemented carbide may be 100% by volume or less. From the viewpoint of manufacturing, the upper limit of the total content of the WC particles and the binder phase of the cemented carbide may be 99% by volume or less, or 98% by volume or less. The total content of the WC particles and the binder phase of the cemented carbide may be 80% by volume or more and 100% by volume or less, 82% by volume or more and 100% by volume or less, or 84% by volume or more and 100% by volume or less.
[0025] The cemented carbide of embodiment 1 can be composed of a plurality of tungsten carbide particles and a binder phase. In addition to the tungsten carbide particles and the binder phase, the cemented carbide of this embodiment can include other phases. The composition of the other phases can include TiCN and TaC.
[0026] The cemented carbide of the first embodiment may be composed of tungsten carbide particles, a binder phase, and other phases. The content of other phases in the cemented carbide is acceptable within a range that does not impair the effects of the present disclosure. For example, the content of other phases in the cemented carbide may be 0 vol.% or more and 20 vol.% or less, 0 vol.% or more and 18 vol.% or less, or 0 vol.% or more and 16 vol.% or less. In this case, the total content of WC particles and binder phases in the cemented carbide may be 80 vol.% or more and less than 100 vol.%, 82 vol.% or more and less than 100 vol.%, or 84 vol.% or more and less than 100 vol.%.
[0027] The cemented carbide of the first embodiment may contain impurities. Examples of the impurities include calcium (Ca) and sulfur (S). The content of impurities in the cemented carbide is acceptable within a range that does not impair the effects of the present disclosure. For example, the content of impurities in the cemented carbide is preferably 0% by mass or more and less than 0.1% by mass. The content of impurities in the cemented carbide is measured by ICP optical emission spectroscopy (measuring device: Shimadzu Corporation "ICPS-8100" (trademark)).
[0028] The lower limit of the content of tungsten carbide particles in the cemented carbide of embodiment 1 may be 60 volume% or more, 62 volume% or more, 64 volume% or more, or 68 volume% or more. The upper limit of the content of tungsten carbide particles in the cemented carbide may be 99.9 volume% or less, 99.2 volume% or less, 99 volume% or less, 98 volume% or less, 96 volume% or less, or 94 volume% or less. The content of tungsten carbide particles in the cemented carbide may be 60 volume% or more and 99.9 volume% or less, 60 volume% or more and 99.2 volume% or less, 64 volume% or more and 96 volume% or less, or 68 volume% or more and 94 volume% or less.
[0029] The cemented carbide of the first embodiment contains a binder phase of 0.1 volume % or more and 20 volume % or less. The lower limit of the binder phase content of the cemented carbide is 0.1 volume % or more, 1 volume % or more, 2 volume % or more, 3 volume % or more, 4 volume % or more, or 8 volume % or more from the viewpoint of improving toughness. The upper limit of the binder phase content of the cemented carbide is 20 volume % or less, 19 volume % or less, 18 volume % or less, 17 volume % or less, 16 volume % or less, or 15 volume % or less from the viewpoint of improving hardness. The binder phase content of the cemented carbide may be 0.1 volume % or more and 18 volume % or less, 1 volume % or more and 18 volume % or less, 3 volume % or more and 17 volume % or less, 4 volume % or more and 16 volume % or less, or 8 volume % or more and 15 volume % or less. When the content of the binder phase in the cemented carbide is 18 volume % or less, the hardness and wear resistance of the cemented carbide are further improved, and therefore the tool life of a cutting tool using the cemented carbide as a material is further improved.
[0030] The method for measuring the content (volume %) of tungsten carbide particles in the cemented carbide and the content (volume %) of the binder phase in the cemented carbide is as follows.
[0031] (A1) An arbitrary position of the cemented carbide is cut out to expose a cross section, which is then mirror-finished using a cross-section polisher (manufactured by JEOL Ltd.).
[0032] (B1) The mirror-finished surface of the cemented carbide is analyzed using a scanning electron microscope-energy dispersive X-ray spectroscopy (SEM-EDX) (apparatus: Carl Zeiss Gemini450 (trademark)) to identify the elements contained in the cemented carbide.
[0033] (C1) The mirror-finished surface of the cemented carbide is photographed with a scanning electron microscope (SEM) to obtain a backscattered electron image. The photographed area is set to the center of the cross section of the cemented carbide, that is, a position that does not include areas with properties that are clearly different from the bulk part, such as the surface area of the cemented carbide (a position where the entire photographed area is the bulk part of the cemented carbide). The observation magnification is 5000x. The measurement conditions are an acceleration voltage of 3kV, a current value of 2nA, and a working distance (WD) of 5mm.
[0034] (D1) The photographed region of (C1) above is analyzed using an energy dispersive X-ray analyzer attached to a SEM (SEM-EDX), the distribution of the elements identified in (B1) above in the photographed region is identified, and an element mapping image is obtained.
[0035] (E1) The backscattered electron image obtained in (C1) above is imported into a computer and binarized using image analysis software (OpenCV, SciPy). In the binarized image, tungsten carbide particles are shown in white, and the bond phase is shown in gray to black. Note that the binarization threshold changes depending on the contrast, so it is set for each image.
[0036] (F1) By superimposing the element mapping image obtained in (D1) above and the image after the binarization process obtained in (E1) above, the respective regions of the tungsten carbide particles and the binder phase are identified on the image after the binarization process. Specifically, the regions shown in white in the image after the binarization process and in which tungsten (W) and carbon (C) exist in the element mapping image correspond to the regions of the tungsten carbide particles. The regions shown in gray to black in the image after the binarization process and in which cobalt (Co) exists in the element mapping image correspond to the regions of the binder phase.
[0037] (G1) A rectangular measurement field of view of 24.9 μm × 18.8 μm is set in the image after the binarization process. Using the image analysis software, the area percentages of the tungsten carbide particles and the binder phase are measured with the area of the entire measurement field as the denominator.
[0038] (H1) The measurement of (G1) above is carried out in five different non-overlapping measurement fields. In this specification, the average of the area percentages of tungsten carbide particles in the five measurement fields corresponds to the content (volume %) of tungsten carbide particles in the cemented carbide, and the average of the area percentages of the binder phase in the five measurement fields corresponds to the content (volume %) of the binder phase in the cemented carbide.
[0039] If the cemented carbide contains other phases in addition to the WC particles and the binder phase, the content of the other phases in the cemented carbide can be obtained by subtracting the content (volume %) of the tungsten carbide particles and the content (volume %) of the binder phase measured by the above procedure from the total cemented carbide (100 volume %).
[0040] As far as the applicant has measured, as long as measurements are performed on the same sample, the cut-out location of the cemented carbide cross section, the photographing area described in (C1) above, and the measurement field of view described in (G1) above can be arbitrarily set, and even if the tungsten carbide particle content and the binder phase content of the cemented carbide are measured multiple times according to the above procedure, there is little variation in the measurement results, and it has been confirmed that the cut-out location of the cemented carbide cross section, the photographing area, and the measurement field of view can be arbitrarily set without being arbitrary.
[0041] <Tungsten carbide particles> In the first embodiment, the tungsten carbide particles include at least one of "pure WC particles (including WC containing no impurity elements and WC containing impurity elements below the detection limit)" and "WC particles containing impurity elements intentionally or unavoidably, as long as the effect of the present disclosure is not impaired." The content of impurities in the tungsten carbide particles (when two or more elements are included as impurities, the total concentration of the elements) is less than 0.1% by mass. The content of impurities in the tungsten carbide particles is measured by ICP emission spectrometry.
[0042] In the first embodiment, the average particle size of the tungsten carbide particles is not particularly limited. The average particle size of the tungsten carbide particles can be, for example, 0.1 μm or more and 3.5 μm or less. It has been confirmed that the cemented carbide of the first embodiment can have a long tool life regardless of the average particle size of the tungsten carbide particles.
[0043] <Binded phase> In the first embodiment, the binder phase contains 50% by mass or more of cobalt. This can impart excellent toughness to the cemented carbide. The lower limit of the cobalt content of the binder phase may be 52% by mass or more, 57% by mass or more, 60% by mass or more, or 63% by mass or more. The upper limit of the cobalt content of the binder phase may be 100% by mass or less, less than 100% by mass, 99% by mass or less, 98% by mass or less, 95% by mass or less, or 90% by mass or less. The cobalt content of the binder phase may be 50% by mass or more and less than 100% by mass, 60% by mass or more and 99% by mass or less, or 63% by mass or more and 98% by mass or less.
[0044] The method for measuring the cobalt content of the binder phase is as follows. Using the same methods as (A1) to (F1) for measuring the tungsten carbide particle content, binder phase content, and hard phase particle content of the above-mentioned cemented carbide, the region in which the binder phase exists is identified on the image after the binarization process. The region in which the binder phase exists is analyzed using SEM-EDX to measure the cobalt content of the binder phase.
[0045] As far as the applicant has measured, as long as the same sample is measured, even if the cut-out portion of the cross section of the cemented carbide and the photographed area described in (C1) above are arbitrarily set and the cobalt content of the binder phase is measured multiple times according to the above procedure, there is little variation in the measurement results, and it has been confirmed that arbitrarily setting the cut-out portion of the cross section of the cemented carbide and the photographed area is not arbitrary.
[0046] In the first embodiment, the binder phase may contain at least one first element selected from the group consisting of boron (B), aluminum (Al), silicon (Si), iron (Fe), nickel (Ni), germanium (Ge), ruthenium (Ru), rhenium (Re), osmium (Os), iridium (Ir) and platinum (Pt) in addition to cobalt. The binder phase may be composed of cobalt, the first element and inevitable impurities. Examples of the inevitable impurities include manganese (Mn), magnesium (Mg), calcium (Ca), and sulfur (S).
[0047] <Vanadium> The cemented carbide of the first embodiment contains vanadium in an amount of 0.03 atomic % or more and 0.90 atomic % or less. The lower limit of the vanadium content of the cemented carbide is 0.03 atomic % or more, may be 0.10 atomic % or more, may be 0.20 atomic % or more, or may be 0.30 atomic % or more, from the viewpoint of improving the grain growth suppression effect. The upper limit of the vanadium content of the cemented carbide is 0.90 atomic % or less, may be 0.80 atomic % or less, or may be 0.70 atomic % or less, from the viewpoint of suppressing the precipitation of a coarse (W, V) C phase. The vanadium content of the cemented carbide may be 0.10 atomic % or more and 0.90 atomic % or less, may be 0.20 atomic % or more and 0.80 atomic % or less, or may be 0.30 atomic % or more and 0.70 atomic % or less.
[0048] The vanadium content of the cemented carbide is measured by ICP emission spectrometry.
[0049] <Chrome> The cemented carbide of the first embodiment contains chromium in a range of 0.01 atomic % to 1.20 atomic %. The lower limit of the chromium content of the cemented carbide is 0.01 atomic % or more, may be 0.10 atomic % or more, or may be 0.20 atomic % or more, from the viewpoint of improving the grain growth suppression effect. The upper limit of the chromium content of the cemented carbide is 1.20 atomic % or less, may be 0.80 atomic % or less, or may be 0.70 atomic % or less, from the viewpoint of suppressing the precipitation of a coarse (W, Cr)C phase. The chromium content of the cemented carbide may be 0.10 atomic % to 0.80 atomic % or less, or may be 0.20 atomic % to 0.70 atomic %.
[0050] The chromium content of the cemented carbide is measured by ICP emission spectrometry.
[0051] <Line Analysis> In the cemented carbide of the first embodiment, the line analysis is performed along the first direction from a position X1 in the tungsten carbide particle to a position X2 in the binder phase adjacent to the tungsten carbide particle, using an energy dispersive X-ray spectrometer attached to a transmission electron microscope. The results are described with reference to Fig. 2. Fig. 2 is an example of a first graph showing the results of performing a line analysis of the cemented carbide of the first embodiment on tungsten, cobalt, vanadium and cobalt, which are elements contained in the cemented carbide, in a coordinate system in which the X axis is the distance from the position X1 and the Y axis is the intensity. In the cemented carbide shown in Fig. 2, the binder phase is cobalt.
[0052] As shown in FIG. 2, in the first region of the first graph, the maximum intensity I W Distance P at W and maximum intensity I W 70% of the strength I W70 The maximum distance P W70 and the maximum strength of vanadium I V Distance P at V and the maximum strength of chromium I Cr Distance P at Cr and the maximum intensity of cobalt I Co 70% of the strength I Co70 The smallest distance P that indicates Co70 and maximum intensity I Co Distance P at Co By P W <P W70 <P V <P Cr <P Co70 <P Co Here, the first region is the region in the first graph where the X axis is P V From the distance P1, which is 3 nm from the origin of the coordinate system, V The area is between the distance P1 and the distance P2, which is 3 nm away from the origin. W70 The first graph shows the intensity I W70 If there are multiple distances that indicate W70 In the first graph of Figure 2, the intensity I W70There are four distances that satisfy the minimum distance P Co70 The first graph shows the intensity I Co70 If there are multiple distances that satisfy the above condition, the smallest distance among them is the distance P Co70 In the first graph of Figure 2, the intensity I Co70 There is one distance that indicates
[0053] P W <P W70 <P V <P Cr <P Co70 <P Co Among the relationships, P W <P V <P Cr <P Co The relationship is that in the first region including the interface between the WC grains and the binder phase, the distance P V The maximum vanadium concentration region is located at a distance P Cr This indicates that the region of maximum chromium concentration is closer to the WC particles than the region of maximum chromium concentration located at 0.1 mm above the WC grains, and that the region of maximum chromium concentration is closer to the binder phase than the region of maximum vanadium concentration.
[0054] P W70 <P V The relationship is distance P V This shows that the maximum concentration region of vanadium located at P is located outside the WC grains and not inside the WC grains. Cr <P Co70 The relationship shows that the maximum concentration of chromium is located outside the binder phase, not inside it. W70 <P V <P Cr <P Co70 The relationship indicates that the maximum vanadium concentration region and the maximum chromium concentration region exist in the interface region between the WC grains and the binder phase.
[0055] In the present disclosure, the line analysis of the cemented carbide and the acquisition of the first graph based on the analysis results are performed as follows: The cemented carbide is sliced to a thickness of 30 to 100 nm using an argon ion slicer ("Cryo Ion Slicer IB-09060BCIS" (trademark) manufactured by JEOL Ltd.) under conditions of an acceleration voltage of 6 kV and finishing of 2 kV to prepare a measurement sample. Next, the measurement sample is observed at 200,000 times magnification using a TEM (Transmission Electron Microscopy) ("JEM-ARM300F2" (trademark) manufactured by JEOL Ltd.) under conditions of an acceleration voltage of 200 V to obtain a first image (not shown).
[0056] In the first image, the tungsten carbide particles are observed as white areas and the binder phase is observed as black areas. In the first image, the interface between the tungsten carbide particles and the binder phase is arbitrarily selected.
[0057] Next, the selected interface is positioned so as to pass through the center of the image, and the observation magnification is adjusted so that the field of view size is 5 nm x 5 nm, and a second image is obtained (not shown). In the second image, the extension direction of the interface is confirmed. Line analysis is performed along a first direction perpendicular to the extension direction and extending from a position X1 in the tungsten carbide particle to a position X2 in the bond phase adjacent to the tungsten carbide particle using an energy dispersive X-ray spectrometer (TEM-EDX) attached to a transmission electron microscope, and the distribution of tungsten, cobalt, vanadium, and chromium is measured. Here, the direction perpendicular to the extension direction of the interface means the direction along a straight line that intersects with the tangent of the extension direction at an angle of 90°±5°. The conditions for EDX are an acceleration voltage of 200 kV, a camera length of 10 cm, a pixel count of 128×128 pixels, and a dwell time of 0.02 to 3 s / pixel.
[0058] A first graph is obtained by plotting the measurement results for each of tungsten, cobalt, vanadium and chromium in a coordinate system in which the X-axis represents the distance from position X1 and the Y-axis represents the intensity.
[0059] In the cemented carbide, five first images of fields not overlapping with each other are arbitrarily obtained, and the above-mentioned analysis is performed based on each of the first images to obtain five first graphs. In the first region of four or more of the first graphs, P W <P W70 <P V <P Cr <P Co70 <P Co When the relationship is shown, in the first region of the first graph of the cemented carbide, P W <P W70 <P V <P Cr <P Co70 <P Co In order to obtain this criterion, the inventors performed multiple line analyses on each of a number of cemented carbide alloys. As a result, in the first graph of 80% or more of these cemented carbide alloys, the relationship W <P W70 <P V <P Cr <P Co70 <P Co It was confirmed that the cemented carbide exhibited the effect of the present disclosure. Considering the manufacturing method of the cemented carbide, it is presumed that the existence forms of vanadium and chromium in the interface region between the WC particles and the binder phase are almost the same in the same cemented carbide.
[0060] P W <P W70 <P V <P Cr <P Co70 <P Co The relationship between the WC particles, the maximum vanadium concentration region, the maximum chromium concentration region, and the positional relationship of the binder phase in the cemented carbide can also be confirmed in a high-angle annular dark field (HAADF) image of a cross section of the cemented carbide. Figure 3 is an HAADF image of the same area of the cemented carbide shown in the graph of Figure 2. In the HAADF image shown in Figure 3, the higher the atomic concentration, the higher the brightness.
[0061] The image shown by W in Fig. 3 is a HAADF image showing the distribution of tungsten atoms. In the image shown by W in Fig. 3, the area with the highest brightness corresponds to the area of WC particles.
[0062] The image shown as Cr in Figure 3 is a HAADF image showing the distribution of chromium atoms. In the image shown as Cr in Figure 3, the area with the highest brightness corresponds to the area with the maximum concentration of chromium.
[0063] The image shown by V in Fig. 3 is a HAADF image showing the distribution of vanadium atoms. In the image shown by V in Fig. 3, the area with the highest brightness corresponds to the area with the maximum vanadium concentration.
[0064] The image shown by Co in Figure 3 is a HAADF image showing the distribution of cobalt atoms. In the image shown by Co in Figure 3, the area with the highest brightness corresponds to the binder phase area.
[0065] From the images of W, Cr, V, and C in Figure 3, it is confirmed that in the first region including the interface between the WC particle and the binder phase, the region with the maximum vanadium concentration is located closer to the WC particle side than the region with the maximum chromium concentration, and the region with the maximum chromium concentration is located closer to the binder phase side than the region with the maximum vanadium concentration.
[0066] The W and V images in FIG. 3 confirm that the maximum vanadium concentration region is located outside the tungsten carbide particles, not inside the tungsten carbide particles. The Cr and Co images in FIG. 3 confirm that the maximum chromium concentration region is located outside the binder phase, not inside the binder phase. These confirm that in the cemented carbide shown in FIG. 3, the maximum vanadium concentration region and the maximum chromium concentration region are located in the interface region between the WC particles and the binder phase.
[0067] In the first region of the first graph of the cemented carbide of embodiment 1, the maximum strength I V Distance P at V The maximum intensity of vanadium atoms and chromium atoms located at I Cr Distance P atCr The chromium atom located at may be present at the W site of tungsten carbide. A method for confirming this will be explained with reference to FIG.
[0068] FIG. 4 is a graph identical to the first graph shown in FIG. 2. In at least a portion of the first graph, tungsten peaks are periodically present along the X-axis. Based on the portion where the period is clearly confirmed, the average period of the tungsten peaks is determined. Based on the average period, the tungsten peak position P3 is entered in the first graph. In the present disclosure, the peak position P3 corresponds to the position of the W site. In the present disclosure, the C site is present between adjacent peak positions P3.
[0069] In the first graph, the maximum strength of vanadium I V Distance P at V and the maximum strength of chromium I Cr Distance P at Cr In the first graph, the peak position P3 of tungsten and the maximum intensity I of vanadium are identified. V Distance P at V If and overlap, P V It is confirmed that the vanadium atom located at is present at the W site of tungsten carbide. In the first graph, the peak position P3 of tungsten and the maximum intensity I of chromium are Cr Distance P at Cr If and overlap, P Cr It is confirmed that the chromium atom located at is present at the W site of tungsten carbide.
[0070] In the first region of the first graph of the cemented carbide of embodiment 1, the maximum strength I V Distance P at V The maximum intensity of vanadium atoms and chromium atoms located at I Cr Distance P at Cr The chromium atom located at is present in the W site of tungsten carbide and may not be present in the C site.
[0071] <Method of manufacturing cemented carbide> The cemented carbide of this embodiment can be manufactured by carrying out a raw material powder preparation step, a mixing step, a molding step, a sintering step, and a HIP (Hot Isostatic Pressing) step in the above order. Each step will be described below.
[0072] <Preparation process> The preparation step is a step of preparing raw material powders of materials that constitute the cemented carbide material. Examples of raw material powders include tungsten carbide powder (hereinafter also referred to as "WC powder"), cobalt (Co) powder, vanadium carbide (VC) powder, and chromium carbide (Cr3C2) powder. In addition to these raw material powders, nickel (Ni) powder, carbide powder, and carbide powder are also used. tantalum For example, TaC powder, titanium carbonitride (TiCN) powder, etc. can be prepared. These raw material powders can be commercially available. The average particle size of these raw material powders is not particularly limited and can be, for example, 0.1 to 3.0 μm. The average particle size of the raw material powder means the average particle size measured by the FSSS (Fisher Sub-Sieve Sizer) method. The average particle size is measured using a Fisher Scientific "Sub-Sieve Sizer Model 95" (trademark).
[0073] <Mixing process> The mixing step is a step of mixing the raw material powders prepared in the preparation step in a predetermined ratio. A mixed powder in which the raw material powders are mixed is obtained by the mixing step. The mixing ratio of the raw material powders is appropriately adjusted depending on the composition of the target cemented carbide.
[0074] The raw material powders can be mixed by a conventionally known mixing method such as an attritor, a ball mill, or a bead mill. Conventional known conditions can also be used for the mixing conditions. The mixing time can be, for example, 2 hours or more and 20 hours or less.
[0075] After the mixing process, the mixed powder may be granulated as necessary. By granulating the mixed powder, it becomes easier to fill the die or mold with the mixed powder during the subsequent forming process. For granulation, known granulation methods can be applied. For example, commercially available granulators such as spray dryers can be used.
[0076] <Forming Process> The forming process is a process of forming the mixed powder obtained in the mixing process into the shape of a cutting tool (for example, a round bar shape) to obtain a formed body. The forming method and forming conditions in the forming process may adopt general methods and conditions and are not particularly limited.
[0077] <Sintering Process> The sintering process is a process of sintering the formed body obtained in the forming process and then cooling it to obtain a cemented carbide intermediate. The sintering conditions in this embodiment are as follows. First, the formed body is placed in an argon (Ar) atmosphere at a pressure of 2 kPa, heated to 900 °C, and held at 900 °C for 60 minutes (hereinafter also referred to as "the first sintering"). Next, in an argon (Ar) atmosphere at a pressure of 2 kPa, the formed body is heated to 1100 °C and held at 1100 °C for 60 minutes (hereinafter also referred to as "the second sintering"). Next, under vacuum, the formed body is heated to 1350 °C and held at 1350 °C for 60 minutes (hereinafter also referred to as "the third sintering"). Next, the formed body is cooled. For example, the formed body is cooled to 25 °C under the condition of 100 - 400 MPaG in Ar gas. Thereby, a cemented carbide intermediate is obtained.
[0078] <HIP Process> The HIP process is a process of performing HIP treatment on the cemented carbide intermediate. The HIP conditions in this embodiment are as follows. First, a temperature of 1250 °C and a pressure of 10 MPa are applied to the cemented carbide intermediate and held for 30 minutes (hereinafter also referred to as "the first HIP"). Next, a temperature of 1350 °C and a pressure of 200 MPa are applied to the cemented carbide intermediate and held for 30 minutes (hereinafter also referred to as "the second HIP"). Thereby, the cemented carbide of Embodiment 1 can be obtained.
[0079] <Features of the method for manufacturing the cemented carbide according to this embodiment> In this embodiment, the sintering process is performed in three stages including the first sintering, the second sintering, and the third sintering. Furthermore, the HIP process is performed in two stages including the first HIP and the second HIP. The cemented carbide obtained by these processes has a P W <P W70 <P V <P Cr <P Co70 <P Co It is presumed that the relationship between the above sintering conditions and HIP conditions is shown. The inventors of the present invention have newly discovered, as a result of extensive research, that the cemented carbide of the present disclosure can be realized under such sintering conditions and HIP conditions. Note that the sintering conditions and HIP conditions used in this embodiment would not have been adopted by a person skilled in the art, since they would reduce production efficiency.
[0080] In conventional methods for manufacturing cemented carbide, the sintering step is performed in one step, that is, by raising the temperature to a predetermined temperature and maintaining it for a predetermined time. In conventional methods for manufacturing cemented carbide, the HIP step is not performed after the sintering step, or if it is performed, it is performed in one step, that is, by maintaining it at a predetermined temperature and pressure for a predetermined time. In the cemented carbide obtained by the conventional method for manufacturing cemented carbide, vanadium and chromium are randomly arranged in the interface region between the WC particles and the binder phase, and in the first region of the first graph .... W <P W70 <P V <P Cr <P Co70 <P Co does not show the relationship.
[0081] [Embodiment 2: Cutting tool] The cutting tool of this embodiment includes a cutting edge made of the cemented carbide of embodiment 1. In this disclosure, the cutting edge means a part involved in cutting. More specifically, the cutting edge means a region surrounded by a cutting edge ridge and a virtual surface that is 0.5 mm or 2 mm away from the cutting edge ridge toward the cemented carbide side.
[0082] Examples of cutting tools include cutting tools, drills, end mills, indexable cutting tips for milling, indexable cutting tips for turning, metal saws, gear cutting tools, reamers, taps, etc. In particular, as shown in Fig. 5, the cutting tool 10 of this embodiment can exhibit excellent effects in the case of a small diameter drill for processing printed circuit boards. The cutting edge 11 of the cutting tool 10 shown in Fig. 3 is made of the cemented carbide of the first embodiment.
[0083] The cemented carbide of the present embodiment may constitute the entirety of these tools, or may constitute a part of them. Here, "constitute a part" refers to a mode in which the cemented carbide of the present embodiment is brazed to a predetermined position of any substrate to form a cutting edge.
[0084] The cutting tool of this embodiment may further include a hard film covering at least a part of the surface of the substrate made of cemented carbide. The hard film may be made of, for example, diamond-like carbon or diamond.
[0085] The cutting tool of this embodiment can be obtained by forming the cemented carbide of embodiment 1 into a desired shape. EXAMPLES
[0086] The present embodiment will be described in more detail with reference to examples, although the present embodiment is not limited to these examples.
[0087] [Preparation of cemented carbide] Each sample of cemented carbide was prepared according to the following procedure.
[0088] WC powder (average particle size 0.3 μm), Co powder (average particle size 1.0 μm), VC powder, Cr3C2 powder, TaC powder, and TiCN powder were prepared in the ratios shown in the "raw powder" columns of Tables 1 and 2, and mixed in an attritor to obtain a mixed powder. The mixing conditions were a rotation speed of 300 rpm and 180 minutes. The average particle sizes of the VC powder, Cr3C2 powder, TaC powder, and TiCN powder were 0.1 to 3.0 μm.
[0089] [Table 1]
[0090] [Table 2]
[0091] Next, the mixed powder was press-molded to produce a rod-shaped compact, which was then sintered and cooled to obtain a cemented carbide intermediate.
[0092] The sintering conditions for Samples 1 to 18 were as follows. First, the compact was placed in an argon (Ar) atmosphere at a pressure of 2 kPa, heated to 900°C, and held at 900°C for 60 minutes (first sintering). Next, in an argon (Ar) atmosphere at a pressure of 2 kPa, the compact was heated to 1100°C and held at 1100°C for 60 minutes (second sintering). Next, in a vacuum, the compact was heated to 1350°C and held at 1350°C for 60 minutes (third sintering). Next, the compact was cooled to 25°C in Ar gas at a pressure of 200 MPaG. This resulted in a cemented carbide intermediate.
[0093] The sintering conditions for samples 101 to 121 were as follows: the compact was heated to 1350°C in a vacuum and held at 1350°C for 60 minutes. Molded body The mixture was cooled to 25° C. under a pressure of 400 kPaG in Ar gas, thereby obtaining a cemented carbide intermediate.
[0094] Next, the cemented carbide intermediate was subjected to HIP treatment to obtain each cemented carbide sample.
[0095] The HIP conditions for Samples 1 to 18 were as follows. First, the cemented carbide intermediate was heated to 1250°C and subjected to a pressure of 10 MPa, and held for 30 minutes (first HIP). Next, the cemented carbide intermediate was heated to 1350°C and subjected to a pressure of 200 MPa, and held for 30 minutes (second HIP). Thus, cemented carbide samples 1 to 18 were obtained.
[0096] The HIP conditions for Samples 101 to 121 were as follows: A temperature of 1300° C. and a pressure of 10 MPa were applied to the cemented carbide intermediate body, and the applied pressure was maintained for 60 minutes. Thus, the cemented carbide of Samples 101 to 121 was obtained.
[0097] [Cutting tool manufacturing] The obtained round bar made of cemented carbide was machined to produce a drill for machining printed circuit boards (PCB (Printed Circuit Board) drill) having a cutting edge diameter of φ0.15 mm.
[0098] [Evaluation of cemented carbide] <Content (volume %) of tungsten carbide particles and binder phase (volume %) of cemented carbide> The content (volume %) of tungsten carbide particles and the content (volume %) of the binder phase of the cemented carbide of each sample were measured. The specific measurement method is as described in embodiment 1. The results are shown in the "WC particle content" and "binder phase content" columns of "carbide" in Tables 3 and 4. Furthermore, the total content of tungsten carbide particles and binder phase of the cemented carbide is shown in the "WC particle + binder phase content" column of "carbide" in Tables 3 and 4. In Tables 3 and 4, it was confirmed that cemented carbide with a "WC particle + binder phase content" column of less than 100 volume % contained TiCN, TiC, etc.
[0099] <Cobalt content in binder phase> The cobalt content in the binder phase of each cemented carbide sample was measured. The specific measurement method is as described in embodiment 1. The results are shown in the "Co content in binder phase" column of "Cemented carbide" in Tables 3 and 4. In Tables 3 and 4, it was confirmed that the binder phase with a "Co content in binder phase" column of less than 100 mass% contained inevitable impurities such as Ni.
[0100] <Vanadium and chromium content in cemented carbide> The vanadium content and chromium content of each cemented carbide sample were measured. The specific measurement method is as described in embodiment 1. The results are shown in the "V content" and "Cr content" columns of "Cemented carbide" in Tables 3 and 4.
[0101] <Line Analysis> The line analysis shown in the first embodiment was performed on each sample of cemented carbide to obtain the first graph. In the first graph of each sample, the maximum strength I W Distance P at W and maximum intensity I W 70% of the strength I W70 The maximum distance P W70 and the maximum strength of vanadium I V Distance P at V and the maximum strength of chromium I Cr Distance P at Cr and the maximum intensity of cobalt I Co 70% of the strength I Co70 The smallest distance P that indicates Co70 and maximum intensity I Co Distance P at Co But, P W <P W70 <P V <P Cr <P Co70 <P Co The results are shown in the "Peak Order" column of Tables 3 and 4. "Yes" means that W <P W70 <P V <P Cr <P Co70 <P Co means that the relationship between W <P W70 <P V <P Cr <P Co70 <P Co This means that the relationship between
[0102] Based on the first graph of each sample, the maximum intensity I of vanadium was measured by the method according to embodiment 1. V Distance P at VThe maximum intensity of vanadium atoms and chromium atoms located at I Cr Distance P at Cr The presence site of the chromium atom located at was confirmed. The results are shown in the "V, Cr presence site" column of Tables 3 and 4. In the "V, Cr presence site" column, "W" indicates that the vanadium atom and the chromium atom are present at the W site of tungsten carbide. In the "V, Cr presence site" column, "W, C" indicates that the vanadium atom and the chromium atom are present at both the W site and the C site of tungsten carbide.
[0103] [Table 3]
[0104] [Table 4]
[0105] [Cutting tool evaluation] <Cutting test> Using each sample PCB drill, holes were drilled into a commercially available printed circuit board for semiconductor packages, and the tool life was evaluated. The printed circuit board was a stack of three 0.4 mm thick boards. The conditions for the drilling process were a rotation speed of 150 krpm, a feed rate of 3 m / min, and a withdrawal rate of 25 m / min. Ten sample PCB drills were prepared, and holes were drilled with each drill, and the number of drills that broke after 10,000 hits was counted. The results are shown in the "Number of drill breakages" column of the "Cutting test" in Tables 3 and 4. The fewer the number of drill breakages, the better the drill's breakage resistance and the longer the tool life.
[0106] <Consideration> The cemented carbide alloys and cutting tools of Samples 1 to 18 correspond to Examples. The cemented carbide alloys and cutting tools of Samples 101 to 121 correspond to Comparative Examples. It was confirmed that the cutting tools of Samples 1 to 18 (Examples) had longer tool life than the cutting tools of Samples 101 to 121 (Comparative Examples). This is presumably because the cemented carbide alloys of Samples 1 to 16 have excellent breakage resistance.
[0107] Although the embodiments and examples of the present disclosure have been described above, it is intended from the outset that the configurations of the above-described embodiments and examples may be appropriately combined or modified in various ways. The embodiments and examples disclosed herein are illustrative in all respects and should not be considered as limiting. The scope of the present invention is indicated by the claims, not by the embodiments and examples described above, and is intended to include the meaning equivalent to the claims and all modifications within the scope. [Explanation of symbols]
[0108] 1 Tungsten carbide particles, 2 binder phase, 3 cemented carbide, 10 cutting tool, 11 cutting edge.
Claims
1. A cemented carbide comprising a plurality of tungsten carbide particles and a binder phase, The cemented carbide contains 80 volume % or more of the tungsten carbide particles and the binder phase in total, The cemented carbide contains the binder phase in an amount of 0.1% by volume or more and 20% by volume or less, The cemented carbide contains vanadium in an amount of 0.03 atomic % or more and 0.90 atomic % or less, The cemented carbide contains 0.01 atomic % or more and 1.20 atomic % or less of chromium, The binder phase contains 50% by mass or more of cobalt, In a first region of a first graph, the results of a line analysis performed using an energy dispersive X-ray spectrometer attached to a transmission electron microscope along a first direction from a position X1 in the tungsten carbide particle to a position X2 in the binder phase adjacent to the tungsten carbide particle are plotted in a coordinate system in which the X axis represents the distance from the position X1 and the Y axis represents the intensity, Maximum strength of tungsten I W Distance P at W and the maximum intensity I W 70% of the strength I W70 The maximum distance P W70 and the maximum strength of vanadium I V Distance P at V and the maximum strength of chromium I Cr Distance P at Cr and the maximum intensity of cobalt I Co 70% of the strength I Co70 The minimum distance P Co70 and the maximum intensity I Co Distance P at Co By P W <P W70 <P V <P Cr <P Co70 <P Co The relationship between The first region is a region in which the X-axis of the first graph corresponds to the P V From the distance P1, which is 3 nm from the origin of the coordinate system, V to a distance P2 at a distance of 3 nm on the opposite side to the origin.
2. 2. The cemented carbide of claim 1, wherein the cemented carbide comprises up to 18% by volume of the binder phase.
3. A cutting tool having a cutting edge made of the cemented carbide according to claim 1 or 2.
Citation Information
Patent Citations
Miniature drill made of cemented carbide excellent in breaking resistance
JP1999350061A
Tough microparticulate cemented carbide
JP2004162080A
Cemented carbide and drill using it
JP2004256852A
Cemented carbide
JP2006131974A
Cemented carbide, cutting tool, and cutting device
WO2009001929A1